Trade and the East Asian Crisis - Hoekman, Bernard; Martin, Will (World Bank, Washington, DC, 2012)
This economic policy note addresses the issue of the East Asian financial crisis, suggesting that recent trade socks, were both a cause and a consequence of this crisis. It further suggests that, though it appears that these trade shocks were largely cyclical in nature, structural changes and policy choices may also have played a role. Dramatic trade changes in the region took place, where the region's overall imports dropped by 4 percent, with a significant 18 percent drop in imports from Japan. Export growth is considered to be a major prospect for short-term economic expansion in the region, depending in part on the composition and pattern of trade flows. The note also suggests that policy implications should be considered, such as heavy investments in education and skills upgrading. Furthermore, macroeconomic policies will be required to capitalize on the initial boost to competitiveness, provided by recent devaluations in the region. The inevitable risk of adjustment pressures in OECD markets exists, though raising barriers should be avoided, since this would harm East Asia's recovery.